Effects of Sodium Hexametaphosphate and Fluoride on the pH and Inorganic Components of Streptococcus mutans and Candida albicans Biofilm after Sucrose Exposure - Hosida, Thayse Yumi [UNESP]; Pessan, Juliano Pelim [UNESP]; Cavazana, Thamires Priscila [UNESP]; Sampaio, Caio [UNESP]; de Morais, Leonardo Antônio [UNESP]; Monteiro, Douglas Roberto [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (MDPI, 2022)
In order to improve the anticaries effects of fluoridated products, the supplementation of these products has been considered a promising alternative for caries control. This study evaluated the effects of sodium hexametaphosphate (HMP) and/or fluoride (F) on the inorganic components and pH of Streptococcus mutans and Candida albicans dual-species biofilms. The biofilms were treated 72, 78, and 96 h after the beginning of their formation with 0.25, 0.5, or 1% HMP-containing solutions with or without F (500 ppm, as sodium fluoride). F-containing solutions (500 ppm and 1100 ppm) and artificial saliva were used as controls. The biofilms were exposed to a 20% sucrose solution after the third treatment. Along with the biofilm pH, the concentrations of F, calcium, phosphorus (P), and HMP were determined. HMP, combined with F, increased F levels and decreased P levels in the biofilm fluid compared to that of the solution with 500 ppm F. Exposure to sucrose decreased the concentrations of all ions in the biomass, except for HMP; 1% HMP, combined with F, promoted the highest pH. It can be concluded that HMP affected the inorganic composition of the biofilm and exerted a buffering effect on the biofilm pH.
Keywords: biofilms; Candida albicans; fluorides; hexametaphosphate; HMP; phosphates; Streptococcus mutans